Bythaelurus vivaldii, a new deep-water catshark (Carcharhiniformes, Scyliorhinidae) from the northwestern Indian Ocean off Somalia - Weigmann, Simon; Kaschner, Carina Julia (Zootaxa, 2017)
A new very small deep-water catshark, Bythaelurus vivaldii, is described based on two female specimens caught off Somalia in the northwestern Indian Ocean during the German ‘Valdivia’ expedition in 1899. It is morphologically closest to the recently described B. bachi, which is the only other Bythaelurus species in the western Indian Ocean that shares a stout body of large specimens and the presence of oral papillae. It further resembles B. vivaldii in the broad mouth and broad posterior head, but differs in the presence of composite oral papillae and a higher diversity in dermal denticle morphology. Additionally, the new species differs from all congeners in the western Indian Ocean in a larger pre-second dorsal fin length, a longer head, a larger interdorsal space, a larger intergill length, a longer pectoral-fin posterior margin, a shorter caudal fin, an intermediate caudal fin preventral margin, and a larger internarial width. Furthermore, the second dorsal fin of the new species is smaller than in its congeners in the western Indian Ocean except for B. lutarius, which is easily distinguished by the slender body and virtual absence of oral papillae, as well as the aforementioned further characters. An updated key to all valid species of Bythaelurus is provided.